Challenges to Language Revitalization: The Efut Perspective - Okon, Margaret Mary; Noah, Paulinus (Soegijapranata Catholic University, 2023)
Efut, a Bantoid language in the Niger-Congo Family, known as Balondo in its ancestral Cameroon homeland, seems to survive on the life support of cultural rituals and Ekpe (‘Leopard’) Society. There is no intergenerational transmission, as language shift is ubiquitous in almost all domains. As a corollary, except Okon Noah (2021), most works underscore only its extinction rather than resuscitation and it is not listed in Ethnologue (2019); hence, part of the momentum for our revitalization effort. From our exploratory investigations, the major challenges to Efut include: aftermath of war, lack of documentation, poor language attitude, linguistic environment, leadership tussle, economic and technological factors. We discuss these issues and suggest stimulus packages towards revitalization. Some of these include proficiency in Efut as a positive reward system and prerequisite for ascendancy to the highest Efut traditional patriarchy (Muri Munene), chieftaincy title awards and free land allocation. The use of social media, optimizing the gains of cultural rituals and Ekpe would serve also as veritable revitalization tools. The paper challenges language enthusiasts and other stakeholders, especially Efut indigenes, to bring fresh perspectives towards revitalizing the language. No human language deserves to die!